European banks are not immune to national elections - Zuzana Fungáčová; Eeva Kerola; Laurent Weill (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2024)
We investigate whether European banks adjust their loan prices and volumes of new lending in the months running up to major national elections. Using a unique dataset that draws on data covering some 250 banksin 19 Eurozone countries from 2010 to 2020 at monthly frequency, and that includes lending amounts and interest rates on new lending, we find that European banks increase loan rates for corporate and housing loans ahead of elections. This supports the view that loan pricing changes of European banks are driven by the electoral uncertainty inherent to the democratic election process. We find that the impact of elections is more pronounced for small banks, as well as obtain some evidence that elections affect the credit supply of banks. Our findings suggest that the occurrence of elections is affecting the behavior of European banks.
urn:nbn:fi-fe202402299216
Keywords: C51; E37; E44; F34; 330; bank; lending; politics; elections; political uncertainty; loan pricing